The Effect of Radio Broadcasting, Nganggung Traditional, Local Influencer, and Education to Sharia Financial Literation’s Level of Central Bangka’s Society - Yaser Taufik Syamlan; Riyan Erwinsyah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
This research was conducted to see the influence of Radio Broadcasts, Traditional Singing, Local Influencers, and Education on the Level of Islamic Financial Literacy in the People of Central Bangka. This type of research is a quantitative study using the regression analysis model. To measure the dependent variable indicators the ordinal scale is used (0-1), and the independent variables are using the Likert scale (1-4). The results of this study indicate that the results of simultaneous testing show that all variables have a significant effect on Islamic financial literacy. This can be seen from the results of the Chi-Square test. However, in the significance test, one of the variables was not significant, namely education, only 3 variables had a significant effect, namely radio broadcasts, local influencers, and culture (nganggung). Based on these statistical results, it can be understood that through radio broadcasts with sharia economic programs, the public gets important information about this matter. Likewise, influential figures such as traditional leaders, community leaders, and religious leaders who have adequate sharia economic insight will contribute to increasing sharia economic literacy. Through the Nganggung Culture, the community will receive this information more quickly.